Algorithm for Correcting the Keratometric Error in the Estimation of the Corneal Power in Keratoconus Eyes after Accelerated Corneal Collagen Crosslinking - David P. Piñero; Vicente J. Camps; Esteban Caravaca-Arens; Dolores de Fez; Francisco J. Blanes-Mompó (Journal of Ophthalmology)
Purpose. To analyze the errors associated to corneal power calculation using the keratometric approach in keratoconus eyes after accelerated corneal collagen crosslinking (CXL) surgery and to obtain a model for the estimation of an adjusted corneal refractive index nkadj minimizing such errors. Methods. Potential differences (ΔPc) among keratometric (Pk) and Gaussian corneal power (PcGauss) were simulated. Three algorithms based on the use of nkadj for the estimation of an adjusted keratometric corneal power (Pkadj) were developed. The agreement between Pk1.3375 (keratometric power using the keratometric index of 1.3375), PcGauss, and Pkadj was evaluated. The validity of the algorithm developed was investigated in 21 keratoconus eyes undergoing accelerated CXL. Results. Pk1.3375 overestimated corneal power between 0.3 and 3.2 D in theoretical simulations and between 0.8 and 2.9 D in the clinical study (ΔPc). Three linear equations were defined for nkadj to be used for different ranges of r1c. In the clinical study, differences between Pkadj and PcGauss did not exceed ±0.8 D nk=1.3375. No statistically significant differences were found between Pkadj and PcGauss (p>0.05) and Pk1.3375 and Pkadj (p<0.001). Conclusions. The use of the keratometric approach in keratoconus eyes after accelerated CXL can lead to significant clinical errors. These errors can be minimized with an adjusted keratometric approach.